Analyzing the Implementation of Islamic Criminal Law in the Nanggroe Aceh Darussalam and Within its Sharia Court - Nasrullah; Nusantara, Muhammad Alwan Zain; Farhansyah, Bagaskara Yonar (Law Review, 2025)
Within the democratic Pancasila system regulated by the Indonesian government, every citizen's right is guaranteed by the government and religious organization to express their beliefs. Aceh, which has enacted regional regulations based on Islamic law and received government support for their implementation, has the freedom to establish its own policies. This study analyzes Aceh's implementation of the Criminal Code (Qanun Jinayah) as well as in its Sharia Court. The case study methodology utilized in this study is intended to provide qualitative data through description-analysis and descriptive qualitative research. According to this study, the execution of Qanun Jinayah in Aceh frequently generates controversy because certain parties believe that the implementation of the law violates human rights, which are normally maintained in democratic countries such as Indonesia. The law applies to both the Muslim and the non-Muslim Achenese. Despite this, numerous parties continue to support the execution of Qanun Jinayah, as they have complied with the exact law recognized by the Indonesian government.